Efektivitas Persepsi Kegunaan, Persepsi Kemudahan, dan Kondisi yang Memfasilitasi Terhadap Keputusan Pembelian - Maf'ula, Eka Riyadhatul; Pebrianggara, Alshaf; Yulianto , Mochamad Rizal (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study analyzes the influence of Perceived Usefulness, Perceived Ease of Use, and Facilitating Conditions on Purchase Decisions among users of the Shopee e-commerce application in Sidoarjo. Employing a quantitative approach, the results indicate that Perceived Usefulness and Perceived Ease of Use have a positive and significant impact on Purchase Decisions, while Facilitating Conditions do not exhibit a significant influence. The findings imply the crucial role of application quality and user-friendliness in enhancing the effectiveness of purchase decisions. Recommendations involve technical improvements to enhance the impact of facilitating conditions. This research provides insights into factors affecting purchase decisions in the e-commerce context, laying the groundwork for further development to enhance user experience and the purchase decision-making process.